Relationship of Urethral Dose and Genitourinary Toxicity Among Patients Receiving Vaginal High Dose Rate Interstitial Brachytherapy. Issue 12 (December 2021) - Cozma, A.I.; Martell, K.; Ravi, A.; Barnes, E.; Donovan, E.; Paudel, M.; Leung, E.; Taggar, A.
Abstract: Aims: Interstitial brachytherapy (ISBT) plays an important role in the management of locally advanced gynaecological malignancies. However, the relationship between urinary toxicity and dose to the urethra is not well understood. We sought to evaluate the correlation between urethral dose and the incidence of genitourinary complications among patients undergoing vaginal high dose rate ISBT. Materials and methods: Eighty-three patients treated with ISBT between August 2014 and April 2018 were retrospectively reviewed. CTCAE version 5.0 was used to grade toxicity. Individual treatment plans were evaluated to collect dose parameters. Urethral contours were added to the structure sets using a uniform 1 cm diameter brush and minimum doses to the hottest 0.1, 0.2 and 0.5 cm 3 (D0.1cm 3, D0.2cm 3 and D0.5cm 3 ) of the urethra were obtained. Total (ISBT ± external beam radiotherapy) equivalent doses in 2 Gy fractions (EQD2) received by the targets and organs at risk were calculated. Numerical counts (%) and medians (interquartile range) were used to characterise the data. Fisher's exact and the Mann–Whitney–Wilcox tests were used as appropriate. Receiver operator curve analysis was used to define the urethral threshold dose that correlated to genitourinary toxicity. Results: The median age and follow-up times were 67 years (59–75) and 25 months (16–37), respectively. Patients had predominantly primary endometrial (49%) and vaginal (37%) cancer, with four (5%) patients with metastatic rectal cancer to the vagina. Twenty-four of 79 (30%) patients experienced acute genitourinary toxicity and 34 of 71 (48%) experienced late genitourinary toxicity. In both analyses, the median urethral dose was significantly higher among those with toxicity. Receiver operator curve analysis indicated that D0.1cm 3, D0.2cm 3 and D0.5cm 3 of the urethra were associated with the development of toxicity at doses >78, >71 and >62 Gy, respectively. Conclusion: Urethral dose seems to predict genitourinary toxicity in ISBT of vaginal tumours. Further study with an expanded cohort and longer follow-up is warranted. Highlights: A review of 83 patients, treated with high dose rate interstitial brachytherapy, at a tertiary centre in Canada. Urethral D0.1cm 3, D0.2cm 3 and D0.5cm 3 correlated with the development of acute and late genitourinary toxicity. This report supports the growing evidence in favour of establishing dose constraints for the urethra in HDR brachytherapy. Prospective trials using patient-reported outcomes are needed to validate results of this study.